Research on the Micromechanical Properties of Minerals and Their Interfaces in Fractured Shale Reservoirs - Mengru Hou; Weiji Sun; Bing Liang; Jianfeng Hao; Qi Liu (Energy Science & Engineering)
ABSTRACT The mechanical properties of shale are key parameters affecting shale reservoirs. They influence the gas content in the shale reservoirs, expansion of hydraulic fractures, and microscopic changes in the in‐situ stress. In this paper, the shale of Longmaxi Formation in Changning area of Sichuan Basin is taken as the research object. The method of constructing shale stochastic microscopic numerical model is investigated by means of scanning electron microscope experiments and image analysis. Shale microscopic modeling was performed in terms of different mineral interface morphology with and without natural fractures. A cohesion model based on the traction–separation law was developed using the finite element method to study the effects of interface morphology and fracture distribution on the micromechanical properties of the shale. The results showed that shales with similar mineral fractions and contents have different mineral interface patterns and inhomogeneities. When a shale is quartz‐rich, linear interfaces are more favorable to brittle damage than curved interfaces. The natural fractures affect the deformability of the shale. The higher the fractal dimension of the fractures, the greater the inhomogeneity and prevalence of microfractures. As the fractures expand, their potential to open and penetrate the natural fractures favors strength reduction and brittle damage of shale. These results provide an important theoretical basis for studying the effects of inhomogeneity on the deformation and strength of shale reservoirs. The hydraulic fracturing of shale reservoirs for enhanced production and hydrocarbon recovery is of practical significance.